Формування комунікативної культури операторів поліції “102” на етапі післядипломної освіти - Гіренко, С. П.; Girenko, S. P.; Червоний, П. Д.; Chervonyi, P. D.; Сергій Гіренко; Павло Червоний (Педагогіка формування творчої особистості у вищій і загальноосвітній школах : зб. наук. пр. – Запоріжжя : КПУ, 2017. – Вип. 52 (105). – С. 446-455, 2017)
У статті розглянуто деякі професійно-педагогічні аспекти психологічної комунікативної підготовки працівників контакт-центрів поліції “102” у післядипломній освіті. Проаналізовано сучасні відомчі вимоги до працівників поліції щодо професійної комунікації із громадянами, головні її принципи та цінності. Зазначено змістовні компоненти ефективної особистісної комунікації із заявниками в типових службових ситуаціях, проаналізовано педагогічні механізми розвитку особистого комунікативного потенціалу працівників контакт-центрів і формування їх професійної культури спілкування з громадянами. Представлено навчальний зміст програми тренінгу “Ефективна комунікація” для працівників контакт-центрів поліції.

The article discusses some of the professional-pedagogical aspects of the psychological communicative training of personal of the contact centers of the police “102” in postgraduate education. The author notes that the relevance of the problem of professional training of police officers is due to focus public attention on today’s law enforcement reform, the need for closer interaction between the police and citizens to reduce the level of crime in the country. The current departmental requirements for employees of the police regarding professional communication with citizens, its main principles and values have been analyzed. There are provided meaningful components of an effective personal communication with the applicants in a typical office situations, analyzed pedagogical mechanisms of personal and communicative potential employees of contact centers and the formation of their professional culture of communication with citizens in the article. There are identified a socio-pedagogical and psychological factors that reflect the relationship of the communicative culture of the teacher and the effectiveness of postgraduate training of police officers. The training content of the training program “Effective communication” for employees of the contact centre to the police has been established. Attention is focused on a factors that determine the professional communication of employees of contact centers, namely: high intensity calls, occupational stress and ways of its prophylactic, increasing conflict applicants and work with objections.

В статье рассмотрены некоторые профессионально-педагогические аспекты психологической коммуникативной подготовки сотрудников контакт-центров полиции “102” в последипломном образовании. Проанализированы современные ведомственные требования к работникам полиции относительно профессиональной коммуникации с гражданами, главные ее принципы и ценности. Указаны содержательные компоненты эффективной личностной коммуникации с заявителями в типичных служебных ситуациях, проанализированы педагогические механизмы развития личного коммуникативного потенциала работников контакт-центров и формированию их профессиональной культуры общения с гражданами. Представлено учебное содержание программы тренинга “Эффективная коммуникация” для сотрудников контакт-центров полиции.
Формирование коммуникативной культуры операторов полиции “102” на этапе последипломного образования
Formation of Communicative Culture of the Police’s “102” Operators at the Stage of Postgraduate Education
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; поліція; полиция; police; комунікація; конфлікт; комунікативна культура; тренінг; професійний стрес; communication; conflict; communication culture; training; professional stress; оператор служби 102; коммуникация; конфликт; коммуникативная культура; тренинг; профессиональный стресс